Equal emissions per capita over time: A proposal to combine responsibility and equity of rights - Sven Bode (Hamburg Institute of International Economics (HWWA), 2003)
After Future climate policy regimes may be based on the Kyoto-Protocol or on other policy instruments such as carbon-taxes. Any effective regime based on the Protocol requires the determination of the concrete contributions by each Party. This involves namely the time of contribution and the quantification of the contribution itself. By now many proposals exist for the two issues, as for example thresholds like GDP per capita for the question of timing or emissions per capita for an allocation of emission rights. Based on the two justice principle responsibility and equity of rights that form the basis for the so-called Brazilian Proposal and Contraction & Convergence respectively, a new approach is developed: Future emission rights are allocated on the basis of equal emissions per capita over time. By so doing not only are emissions per capita (EPC) taken into account during the allocation but also their evolution over time. I show that nations with high EPC may even be allocated negative quantities of emissions right due to their historical ?burden?. On the other hand, Parties with low EPC would be allocated large amounts of ?fair air? which can increase the incentive to accept absolute emission targets. Even though this approach may currently lack political acceptability, it offers another analytical reference point for the political bargaining process on future allocations.
Keywords: Q28; Q25; 330; allocation of GHG emission entitlements; Brazilian Proposal; CDM; Contraction & Convergence; equity; post 2012 climate regime; Klimaschutz; Emissionsrechte; Verantwortung; Gerechtigkeit; Sozialprodukt; Welt